KEMAMPUAN KONEKSI MATEMATIS SISWA DALAM MATERI BARISAN DAN DERET ARITMATIKA DI SEKOLAH MENENGAH ATAS - Petronela, Rini; Jamiah, Yulis; Sayu, Silvia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to describe the students’ ability of making connection in arithmetic sequences and series material at senior high school in academic year 2017/2018. Method used in this research was descriptive in case study form. Subject in this research were the twelfth grade of SMA Negeri 8 Pontianak with a number of 34 students. Data collection technique used were test and interview. The result of data analysis showed students’ mathematical connection ability were varied; some students were in the high category while the others were in the medium or low category. However, the students’ ability to recognize and use connections among mathematical and to recognize and apply mathematic concepts in daily activity generally were on the medium category with each percentage 65.44% and 63.24%. The students whom were on the medium and low category couldn’t use connections among mathematical concepts because they didn’t understand about the arithmetic sequences and series material. They also couldn’t apply mathematic concepts in daily activity because they seldom solve the problems about their daily activities.Keywords: Connection Ability, Arithmetic Sequences and Series